Efficiency enhancement of ZnO/Cu2O solar cells with well oriented and micrometer grain sized Cu2O films - Zang, Zhigang (Applied physics letters, 2018)
Cu2O is one of the attractive photovoltaic materials for solar cells because of its low cost, nontoxicity, and good mobility. In this paper, an obvious enhancement of power conversion efficiency (PCE) for ZnO/Cu2O solar cells with perfectly oriented and micrometer grain sized Cu2O films was experimentally demonstrated. Cu2O was fabricated using radical oxidation of Cu foils at a low temperature of 500 °C. When followed by a rapid quenching and post annealing treatment, the perfectly oriented and micrometer sized Cu2O crystals (3∼4 μm) could be obtained. The crystal structure and optical properties of Cu2O were investigated in detail. Compared to conventional solar cells without any treatment, the PCE of the solar cells based on Cu2O with treatment was 3.18%, corresponding to a significant PCE improvement of 60.6%.